Progress in resource management and environmental planning. - D'Arge, Ralph C.; O'Riordan, Timothy (Chichester, Eng. Wiley, 1979)
Irregular.
Editors: v. 1- T. O'Riordan and R. C. D'Arge.
Keywords: Social policy -- Periodicals